2008
DOI: 10.3109/s10165-008-0057-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of retinal vasculitis in Behçet's disease with rituximab

Abstract: Behçet's disease (BD) is more common in eastern than western countries. Physicians have frequently encountered problems in its treatment, especially eye involvement. Recurrent oral and genital aphthous ulcerations are the hallmarks of Behçet's disease but other organs can be involved and ocular disease is one of the most disabling manifestations. Up to now, there are some problems in treatment of the retinal vasculitis due to Behçet's disease. We reported one patient, with visual loss due to retinal vasculitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Case report [Belzunegui et al 2008] Vascular involvement Case report [Lee et al 2010] Rituximab Eye involvement Case report [Sadreddini et al 2008] Randomized single-blind study [Davatchi et al 2010] Gevokizumab Eye involvement Open label study [Gul et al 2012] Canakinumab Eye involvement Case report [Ugurlu et al 2012] Extraocular disease Case report Anakinra Extraocular disease Case report [Botsios et al 2008] Tocilizumab Neuro-Behçet Case reports [Urbaniak et al 2012;Shapiro et al 2012] Eye involvement Case report [Hirano et al 2012] …”
Section: Neuro-behçetmentioning
confidence: 99%
“…Case report [Belzunegui et al 2008] Vascular involvement Case report [Lee et al 2010] Rituximab Eye involvement Case report [Sadreddini et al 2008] Randomized single-blind study [Davatchi et al 2010] Gevokizumab Eye involvement Open label study [Gul et al 2012] Canakinumab Eye involvement Case report [Ugurlu et al 2012] Extraocular disease Case report Anakinra Extraocular disease Case report [Botsios et al 2008] Tocilizumab Neuro-Behçet Case reports [Urbaniak et al 2012;Shapiro et al 2012] Eye involvement Case report [Hirano et al 2012] …”
Section: Neuro-behçetmentioning
confidence: 99%
“…[38] The results of this study revealed significantly higher levels of the serum BAFF in the Behçet's group in comparison with the control group. To our knowledge, there are no previously available recorded levels of the serum BAAF in BD patients, but Sadreddini et al [16] reported successful treatment of a resistant case of retinal vasculitis with rituximab, which acts against the specific B cell antigen (CD20). This indicates that B cells must have a much broader role in the pathogenesis of BD.…”
Section: Discussionmentioning
confidence: 99%
“…The recent success of rituximab in cases of autoimmune diseases which are considered to be T cell-mediated, like BD, indicates that B cells must have a much broader role in the pathogenesis of this disease than has been previously thought. [16] The aim of this study was to determine and compare the serum level of the BAFF in patients with RA, SLE, and BD and also to correlate its serum level with disease activity indices and severity.…”
mentioning
confidence: 99%
“…Rituximab has been successfully used for the treatment of refractory keratoconjunctivitis, scleritis [18][19][20][21][22][23], peripheral ulcerative keratitis [24,25], uveitis [26][27][28][29] and ocular surface inflammatory diseases such as cicatricial pemphigoid [30,31] also when associated with systemic diseases. Experience in inflammatory ocular diseases is still scarce with few case reports on its efficacy.…”
Section: Rituximab In Inflammatory Eye Diseasesmentioning
confidence: 99%
“…Davatchi and Sadreddini showed favorable results on the efficacy of Rituximab in intractable ocular lesions of patients with Behcet's disease, in spite of the fact that it is mainly a T-cell driven disease [27,28].…”
Section: Uveitismentioning
confidence: 99%